THE ROLE OF STARTUP ACCELERATORS IN THE FORMATION AND DEVELOPMENT OF INNOVATIVE ENTREPRENEURSHIP - Lizaveta Peniaz (Izdevnieciba "Baltija Publishing", 2023)
The research is dedicated to exploring the significant impact that startup accelerators have on the growth and development of innovative entrepreneurship. It examines how these accelerators support emerging businesses, particularly in the areas of technology and innovation. The study aims to critically analyse and articulate the integral role of startup accelerators in fostering AI-driven entrepreneurship, thereby contributing to a broader understanding of their impact on the innovation ecosystem. The research findings indicate that accelerator programs are instrumental in the growth of AI startups, contributing more than just financial aid. They offer crucial strategic advice, mentorship, and access to broad networks. A notable example is the success of AI startups like OpenAI, which have flourished under these programs, gaining substantial funding and high market valuations. This underscores the role of accelerator programs in fostering industry innovation and growth. AI-focused entrepreneurial ventures are expected to have a significant impact on the global economy and technological progress. By 2030, they are expected to contribute around 16 trillion USD to global GDP, primarily driven by productivity gains, personalisation and quality improvements. Innovation development policies, particularly in AI, have a profound impact on the global redistribution of human capital, particularly in terms of talent acquisition and innovation. Initiatives aimed at strengthening AI talent and facilitating visa processes are critical to attracting global talent, thereby boosting the innovative capabilities of these startups. The race for intellectual capital is predominantly among major players such as the US, China and the UK. The study provides valuable insights for entrepreneurs and investors, highlighting how accelerator programmes can effectively support startup growth and innovation, especially in emerging technology areas such as AI.